Analisis Praktik Penganggaran Dan Penyaluran Bantuan Dana Desa Untuk Penanganan Pandemi Covid-19 Pada Desa Pejeng Kawan, Kecamatan Tampaksiring, Kabupaten Gianyar - Desak Putu Eva Meitayani; Putu Fery Karyada; Rai Dwi Andayani W (Hita Akuntansi dan Keuangan, 2022)
As a result of the Covid-19 pandemic, various government measures have been issued to deal with the virus's transmission and treatment. Changes to the village fund budget for activities to combat the Covid-19 pandemic and for social safety nets in villages, in the form of Direct Cash Assistance, are among the proposals announced by the government (BLT). The main purpose of this study is to analyze village fund management during the Covid-19 pandemic and to find ways to provide village fund assistance. The method used in this research is a qualitative research method with a descriptive approach. Several data collection approaches, including as interviews, observation, documentation and triangulation of data sources, are used by the writers to gather accurate and accountable data. The village of Pejeng Kawan in Gianyar Regency's Tampaksiring District was the focus of this investigation. When it came to budgeting and village fund support, the Pejeng Kawan Village Government performed a good job, but there were issues when it came to revising the budget because it didn't include funding for disaster management and Urge the Village so that they are a little confused. Then in the supervision section carried out by the BPD, the BPD has not been carried out optimally, the BPD does not understand the function because as a supervisory body for the Pejeng Kawan Village Government